Perlindungan Hukum terhadap Hak Pasien dalam Pelayanan Kesehatan di Kota Batu - Maradona, Maradona; Silviana Damayanti (LPPM Universitas Ekasakti Padang, 2023)
This study aims to analyze the role of Standard Operating Procedures (SOPs) in protecting the rights of patients at Puskesmas Batu. The research methodology employed is normative law, utilizing legislative and conceptual approaches. Through document analysis and examination of related regulations, this study investigates how SOPs at Puskesmas Batu are designed and implemented to ensure the safeguarding of patient rights, including the right to information, privacy, and access to safe, quality healthcare services. The findings indicate that, although the SOPs at Puskesmas Batu are designed in accordance with national standards, challenges persist in their implementation, notably resource limitations and personnel training. This research provides recommendations for enhancing the SOPs and practices at Puskesmas Batu to optimize patient rights protection.